World Wide Web : an introduction. - HIGGINS, Peter (1996)
Provides a beginner's introduction to the Internet and the World Wide Web. Discusses what the Internet is, and what it is not and its relevance to everyday life. Outlines the development and functions of the World Wide Web, and briefly explains the use of HyperText Markup Language (HTML) to create web pages. Includes a sample web page and its HTML structure, and a glossary of terms.